Complement After Trauma: Suturing Innate and Adaptive Immunity - Chakraborty, Shinjini; Karasu, Ebru; Huber-Lang, Markus (Frontiers in Immunology, 2018)
The overpowering effect of trauma on the immune system is undisputed. Severe trauma, as characterized by systemic cytokine generation, activation of systemic inflammatory immune response and its dysregulation, complementopathy and coagulopathy, has been immensely instrumental in understanding the underlying mechanisms of the innate immune system during systemic inflammation. The compartmentalized functions of the innate and adaptive immune systems are being gradually recognized as an overlapping, interactive and dynamic system of responsive elements. The current knowledge of the complement cascade and its interaction with adaptive immune response mediators and cells, including T- and B-lymphocytes, is limited. In this review, we discuss what is known about the bridging effects of the complement system on the adaptive immune system following trauma and which unexplored areas could prove to be crucial in understanding the link between the complement and adaptive immune systems in trauma.